PENINGKATAN KUALITAS LAYANAN, KELENGKAPAN PRODUK DAN CITRA PERUSAHAAN SEBAGAI UPAYA MEMAKSIMALKAN KEPUASAN KONSUMEN PADA TOKO EL MALIK KABUPATEN SUMENEP - Mohammad Rofik; Unsul Abrar (Fakultas Ekonomi dan Bisnis, 2019)
This research has purpose to know the effect from service quality, product completeness, corporate image on customer satisfaction. Based on there are many competitors of modern retail stores that have sprung up, it is not impossible that a store that used to be big can be a store left by its customers. The quality of service, store completeness and corporate image are the solutions to maximize consumer satisfaction at the Sumenep Elmalik shop. Kind from this research is a quantitative researc with the total of respondents determined by purposive sampling as one hundred respondents. Respondents were divided into several types, namely gender, age and occupation. Technical analiysis uses multiple linear regression. The results explain that quality of service, complecated product and corporate image give affection on Elmalik satisfaction of consumer, this is evidenced by the t value > from t table.